Comparative economic, environmental and productivity assessment of a concrete bathroom unit fabricated through 3D printing and a precast approach. (10th July 2020) - Weng, Yiwei; Li, Mingyang; Ruan, Shaoqin; Wong, Teck Neng; Tan, Ming Jen; Ow Yeong, Kah Leong; Qian, Shunzhi
Abstract: The purpose of this study is to perform a comparative study of economic cost, environmental impacts, and productivity associated with manufacturing a prefabricated bathroom unit (PBU, L: 1620 mm; W: 1500 mm; H: 2800 mm) via extrusion-based 3D concrete printing (3DCP) and a precast approach, respectively. The scope of this study includes material consumption, electricity expenditure, labor cost/productivity, and installation cycle. The results reveal that a PBU fabricated by 3DCP achieves a reduction of 25.4% in overall cost, 85.9% in CO2 emission, and 87.1% in energy consumption compared to the precast one. 3DCP also realizes a PBU with reduced self-weight (i.e., 26.2% lighter) and higher productivity (i.e., 48.1% improved) compared to the precast one. The above enhancements were found to be ascribed to the formwork-free fabrication in 3DCP. Finally, sensitivity analysis reveals the significance of formwork re-usage to the outcomes and demonstrates the potentials of 3DCP for small batches or customized manufacturing of PBUs. Graphical abstract: Image 1 Highlights: Assessment on fabrication of a concrete bathroom unit via 3D concrete printing (3DCP) and precast method was performed. Several indicators such as environmental impact can be improved via 3DCP in construction. Better performance is achieved for 3DCP by eliminating formwork usage. 3DCP can be used for small batches or customized fabrication with versatile design.